Windstorms as mediator of soil nematode community changes: Evidence from European spruce forest - Renčo M.; Čerevková A. (Helminthologia, 2017)
Nematode communities in a Norway spruce forest in High Tatra National Park, Slovakia were monitored for the period of several years (2006 and 2013). Unfortunately, in May 2014 natural windstorm damaged the forest. This disastrous event, together with preliminary obtained results allowed us to compare the direct impact of windstorm damage of forest habitat on soil nematode assemblages. The forest destruction by windstorm had a significant effect on the total nematode abundance, the abundance of omnivores and herbivores, as well as the nematode species diversity. The most dominant species, representing 55 % of the total nematode fauna, in the plot studied were Acrobeloides nanus followed by Malenchus exiguus, Filenchus vulgaris, Plectus communis, Plectus parvus and Tylencholaimus mirabilis. The abundance of bacterivorous signifi cantly increased after the windstorm, meanwhile the abundance of omnivores, fungivores, and herbivores ectoparasites and epidermal/root hair feeders showed an opposite trend. Of the evaluative indicators, Shannon species diversity (H’spp), maturity index (MI), maturity index 2-5 (MI2-5), sigma maturity index (ΣMI), enrichment index (EI) and structure index (SI) decreased significantly after windstorm. The EI and SI indexes characterized soil ecosystems before windstorm (2006 - 2013) as maturing with low or moderate disturbance, but soil ecosystems shortly after the windstorm (2014) were degraded and nutrient depleted. This also corresponded with graphical display of metabolic footprints characteristics of soil food web. Overall, the nematode communities differed significantly before and after forest damage. These results suggest the role of nematode communities as indicators of environment condition quality or its disruption.